2023
DOI: 10.3390/f14061226
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus hamabo Rootstock-Grafting Improves Photosynthetic Capacity of Hibiscus syriacus under Salt Stress

Abstract: Hibiscus syriacus, a woody ornamental plant with great economic value, is vulnerable to salinity. Hence, its cultivation in saline areas is severely restricted. Although grafting H. syriacus onto H. hamabo rootstock can greatly improve H. syriacus’s salt resistance, the photosynthetic response of H. syriacus to grafting and salt stress remains largely unknown. To address this question, self-rooted (Hs), self-grafted (Hs/Hs), and H. hamabo-grafted (Hs/Hh) H. syriacus were exposed to 0 or 300 mM NaCl. Salt signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Saline is one of the most serious abiotic stresses that affecting plant growth and development worldwide [12]. Zhang et al found that grafting can ameliorate the inhibition of salinity on the photosynthetic capacity of Hibiscus syriacus, mainly resulting from alleviated limitations on photosynthetic pigments, photochemical efficiency, and the Calvin-Benson-Bassham cycle [13]. Additionally, the overexpression of the poplar WRKY51 transcription factor was found to enhance salt tolerance in Arabidopsis thaliana, demonstrating the potential of genetic engineering for improving tree resilience [14].…”
Section: Salinitymentioning
confidence: 99%
“…Saline is one of the most serious abiotic stresses that affecting plant growth and development worldwide [12]. Zhang et al found that grafting can ameliorate the inhibition of salinity on the photosynthetic capacity of Hibiscus syriacus, mainly resulting from alleviated limitations on photosynthetic pigments, photochemical efficiency, and the Calvin-Benson-Bassham cycle [13]. Additionally, the overexpression of the poplar WRKY51 transcription factor was found to enhance salt tolerance in Arabidopsis thaliana, demonstrating the potential of genetic engineering for improving tree resilience [14].…”
Section: Salinitymentioning
confidence: 99%